1991
DOI: 10.1103/physrevb.44.9301
|View full text |Cite
|
Sign up to set email alerts
|

Neutron-scattering and electron-microscopy studies of the premartensitic phenomena inNixAl100

Abstract: Inelastic-neutron-scattering and electron-microscopy studies were performed on single crystals of the cubic phase of Ni, A1, 00, alloys for x=50, 58, 62.5, and 63.9 at. %. The [110]-TAz phonon branch, corresponding to atomic displacements along the [110]direction, is shown to exhibit anomalous behavior in that the entire branch is very sensitive to composition and exhibits a "kink" whose position in q space is also sensitive to x. A peak in the elastic diffuse scattering is also present at the same q as the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
80
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(88 citation statements)
references
References 51 publications
7
80
1
Order By: Relevance
“…When the sample is cooled down, this dip becomes more pronounced, but the softening is always incomplete and below a given temperature still above M s the frequency of the soft modes starts to increase again. 9 The prototype alloy system where similar softening effects have been observed is Ni-Al; 13 however, the amount of softening measured in Ni 2 MnGa is larger and in Ni-Al there is not an increase of the frequency below a given temperature. Also, recent measurements by some of the present authors 14 have shown that, at the temperature of phonon condensation, the thermal expansion and elastic modulus versus temperature curves exhibit a minimum, which is accompanied by an increase in the internal friction.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…When the sample is cooled down, this dip becomes more pronounced, but the softening is always incomplete and below a given temperature still above M s the frequency of the soft modes starts to increase again. 9 The prototype alloy system where similar softening effects have been observed is Ni-Al; 13 however, the amount of softening measured in Ni 2 MnGa is larger and in Ni-Al there is not an increase of the frequency below a given temperature. Also, recent measurements by some of the present authors 14 have shown that, at the temperature of phonon condensation, the thermal expansion and elastic modulus versus temperature curves exhibit a minimum, which is accompanied by an increase in the internal friction.…”
mentioning
confidence: 96%
“…Another system showing an intermediate premartensitic structure accompanied by pronounced phonon softening is Ni-Al. 13 The elastic constants of this alloy, however, do not show the aforementioned anomalous behavior. 21 The different behavior in the two alloy systems is due to the existence in Ni 2 MnGa of a phase transition towards the intermediate phase.…”
mentioning
confidence: 97%
“…From this point of view, the "soft mode" phenomenon often referred to as pre-martensitic and cited to be a characteristic of the martensitic transition is not an intrinsic softening of the austenite phase, but rather a collective and effective response of pre-existing martensitic-like embryos stabilized by static defects, such as dislocations and/or grain boundaries or even pinned defects. 34,35,40 Inside the martensitic embryos accommodation cannot be perfect, because the boundary of any finite domain cannot consist exclusively of habit planes. Therefore, elastic screening by twinning is only partial and some unrelaxed elastic energy is stored in the resulting martensitic domain and in its surrounding.…”
Section: A the Martensitic Transition In A Perfect Single Crystalmentioning
confidence: 99%
“…Therefore, the first embryos are essentially modulated or simply sheared as onset for the polytwinned character of the final martensite domain and cannot nucleate homogeneously through thermal fluctuations. 34,35 Nucleation is heterogeneous on pre-existing defects that generate local favorable strains. Note that, to a certain extent, these embryos exist above the equilibrium temperature T 0 and can be responsible for the softness of the effective shear elastic constant often observed experimentally well above T 0 .…”
Section: A the Martensitic Transition In A Perfect Single Crystalmentioning
confidence: 99%
“…These materials are characterized by highly mobile twin boundaries and (often) show precursor structures (e.g., tweed [4][5][6]) above the transition. Furthermore, these materials have small Bain strain, elastic shear modulus softening, and a weakly to moderately first order transition.…”
Section: Introductionmentioning
confidence: 99%